Cost‐savings of adalimumab in hidradenitis suppurativa: a retrospective analysis of a real‐world cohort. (1st May 2019) - Argyropoulou, M.; Kanni, T.; Kyprianou, M.; Melachroinopoulos, N.; Giamarellos‐Bourboulis, E.J.
Summary: Background: The introduction of adalimumab in the management of hidradenitis suppurativa (HS) raises questions regarding the cost‐efficacy of treatment. Objectives: To explore cost‐efficacy of treatment with anti‐tumour necrosis factor (TNF) agents in a real‐world cohort. Methods: Patients with Hurley stage II and III HS with ≥ 1 year of follow‐up and at least three visits per year from September 2003 to December 2016 were analysed. Patient visits were divided into two categories – visits for treatment with agents blocking TNF or visits for other therapies. The cost of exacerbations was calculated based on the cost of items provided in current price lists or by the national health insurance agency in cases of hospitalization. Effectiveness of anti‐TNF agents was calculated by assessing containment of exacerbations. The primary study end point was the cost‐savings achieved using anti‐TNF agents. Results: Overall, 1211 patient visits for 250 patients were analysed. Total containment of exacerbations was found in 25·1% of visits involving other therapies and in 63·4% of visits involving anti‐TNF agents. The cost‐savings per patient visit for patients receiving anti‐TNF agents vs. other therapies was €178·92. The odds ratio for the total containment of exacerbations among patients with Hurley stage II and III was 4·86 and 6·03, respectively ( P = 0·466). Treatment with anti‐TNF agents was an independent variable affecting annual cost as shown by two‐way analysis of variance. In Hurley stage III HS, mean annual cost was €8309·60 under other therapies compared with €3264·20 using anti‐TNF agents ( P = 0·004). Conclusions: Treatment with anti‐TNF agents achieves significant cost–benefit through containment of HS exacerbations. The efficacy of anti‐TNF agents was similar for both disease stages.